Evaluation of Hypoglycemic and Antioxidative Effects of Synthesized Peptide MC62. (21st June 2013) - Yang, Baowei; Chen, Wei; Jin, Jing; Mei, Yicheng; Wang, Xuekun; Chen, Hong; Yan, Sijia; Ru, Meng; Gu, Guolong; Deng, Xin; Qian, Hai; Huang, Wenlong
<x xml:space="preserve">Abstract</x> Diabetes mellitus has been considered as a major health problem in the world today. This study aimed to investigate the hypoglycemic and antioxidative effects of peptide MC62 which was synthesized by solid‐phase peptide synthesis method against diabetes induced by streptozotocin. MC62 was administered daily and injected intraperitoneally to the diabetic mice at a dose of 1 μmol/kg body weight for 20 days. The levels of fasting blood glucose and HbA1C, pancreatic islet damage, and associated changes in antioxidative activities were evaluated in streptozotocin‐induced diabetic mice used the exenatide as positive control. After the administration of MC62 together with exenatide for 20 days, the elevated fasting blood glucose and HbA1C levels were reduced, and antioxidative activities were restored. It was confirmed with the histological finding that MC62 prevented the islet from damage in diabetic mice. This indicated that MC62 can prevent mice from hyperglycemia which may be associated with oxidative stress. It also suggested that MC62 could be used as a safe alternative hypoglycemic candidate for treatment of diabetes.